Prevalence and associated factors of dental caries among 8-12 year-old children in Libyan schools in Klang Valley, Malaysia - Abuaisha, Aisha Ageil Abdullah (2016)
Dental caries is the most common oral disease in children and adults in developed and developing countries and is the main cause of loss of teeth in younger people; it continues to be a major public health concern, dental caries are increasing over time. Libya is one of the few countries that have increased caries prevalence among children. This disease is greatly affected by many risk factors. The objective of this study was to determine the prevalence of dental caries and associated factors among Libyan school children in Klang Valley aged 8 to12 years. A cross-sectional study was conducted among three Libyan schools in Klang Valley. Proportionate stratified sampling method was used to select the children. A total of 570 respondents were selected. Dental caries were assessed using the WHO (1987) criteria. Information about dietary habits, socio-demographic and oral hygiene habits were collected through a dental health questionnaire. Dental examination of children was done using mouth mirror and dental explorer. The data were analyzed using IBM (SPSS) Version 20.0. Chi-square test was used to test the association and to determine the risk factors of dental caries, binary multiple logistic regression analyses were applied. The prevalence of dental caries was 55.8%, females have higher dental caries than males. Dental caries was found highly prevalent among; children aged 10 years (64.7%), children whose fathers and mothers have a job (58.5% and 58.7% respectively), children whose fathers and mothers have elementary level of education (69.6% and 61.0% respectively), children who have poor oral hygiene (99.0%), children who consume high cariogenic food (91.7%), children who consume high cariogenic drinks (95.2%) and children who preferred to eat sweet snacks and sweet drinks at all times (65.7% and 62.9% respectively). Moreover, there were significant association between dental caries with age group, fathers education level, oral hygiene habits; consumption of cariogenic food, consumption of cariogenic drinks and total score of dietary habits, also, young age (OR=11.78, 95% Cl: 2.30-26.27), high cariogenic drinks (OR=9.95, 95% Cl: 2.44-16.97) and poor oral hygiene (OR=8.97, 95% Cl: 4.76-33.29) were predictors for dental caries among children. In conclusion, dietary habits, oral hygiene habits and socio-demographic characteristic are identified as modifiable risk factors that related to dental caries among Libyan school children at age 8-12 years in Malaysia. Health education on good oral hygiene habits should be emphasized among younger Libyan school children.